Sistem Informasi Akademik Universitas Surakarta Berbasis Web - Ayu Fiska Nurryna - Universitas Surakarta (SPEED - Sentra Penelitian Engineering dan Edukasi, 2008)
ABSTRACT: Currently the cultural change has been characterized by the use of the internet isincreasingly global. Internet as an information giver existence has now become a necessity. Theperceived benefits of the internet is big enough, especially in the world of business, entertainment andeducation. University of Surakarta is one of the colleges that have used the Academic InformationSystem although now the system is not connected to the Internet. Therefore, in this study will bedeveloped an Academic Information System Web-Based UNSA.This research aims to make academic information system building Surakarta University with a webbasedso as to provide more benefits to many parties. Among other things from the students can seenew information related to academic activities, from the parents of students can immediately see theactivities or grades of the students concerned, and from the manager of the work so much lighter. Thisstudy will use a structured approach. Software engineering web-based academic information systemcarried out for the system development process so as to cover all the needs.After the authors conducted an analysis on the part of the management of University Study Plan CardSurakarta the results obtained is the analysis of the results of research, analysis and design of theproposed system and the implementation of the Academic Information System Web-based Universityof Surakarta. Expected with the construction of Academic Information System Web-based provision ofinformation then the problem will be resolved mahasisiwa study results. And the University may soondevelop a new system in order to work with the maximum.Keywords: Academic Information System; Web-BasedAbstraksi : Saat ini perubahan budaya telah ditandai dengan adanya pemanfaatan internet yangsemakin mendunia. Internet sebagai penyampai informasi keberadaannya kini sudah menjadikebutuhan. Manfaat internet cukup besar dirasakan terutama dalam dunia bisnis, hiburan danpendidikan. Universitas Surakarta adalah salah satu perguruan tinggi yang telah menggunakanSistem Informasi Akademik walaupun sekarang sistem tersebut belum disambungkan ke intenet. Olehkarena itu, dalam penelitian ini akan dikembangkan suatu Sistem Informasi Akademik UNSA BerbasisWeb.Penelitian ini bertujuan untuk membuat membangun sistem informasi akademik UniversitasSurakarta dengan berbasis web sehingga dapat memberikan manfaat yang lebih kepada banyakpihak. Antara lain dari pihak mahasiswa dapat melihat informasi-informasi baru yang berhubungandengan kegiatan akademik, dari pihak orangtua mahasiswa dapat langsung melihat kegiatan atau nilaidari mahasiswa yang bersangkutan, dan dari pihak pengelola pekerjaan jadi lebih ringan. Penelitianini akan menggunakan metode pendekatan terstruktur. Rekayasa perangkat lunak sistem informasiakademik berbasis web dilakukan untuk proses pengembangan sistem sehingga mampu mencakupsemua kebutuhan.Setelah penyusun melakukan analisis pada bagian pengelolaan Kartu Rencana StudiUniversitas Surakarta maka hasil yang diperoleh adalah analisis dari hasil penelitian, analisis danperancangan untuk sistem usulan dan implementasi Sistem Informasi Akademik UniversitasSurakarta berbasis Web. Diharapkan dengan dibangunnya Sistem Informasi Akademik berbasis webmaka masalah akan penyediaan informasi hasil studi mahasisiwa akan teratasi. Dan pihak Universitasdapat segera mengembangkan sistem yang baru agar dapat bekerja dengan maksimal.Kata kunci: Sistem Informasi Akademik; Berbasis Web